Design of a piezoelectric generator for vibration energy harvesting using non ferroelectric PZnT-NT / Zainab Shakir Radeef - Zainab , Shakir Radeef (2018)
Over the past years, there are a considerable knowledge and continuous striving toward scavenging a sustainable power from piezoelectric harvesters, which convert the waste mechanical energy to useful electrical energy. Among the piezoelectric materials, non-ferroelectric materials are more cost-effective and ease to build using the wet chemical method. In this study, a novel non-ferroelectric was manufactured from 0.7PbZn0.3Ti0.7O3-0.3Na2TiO3 (PZnT-NT) through p-n junction construction. It was demonstrated that the increment of conductivity via adding the Na2TiO3 plays an essential role in increasing the permittivity of the non-ferroelectric harvester and hence improved the generated power density. The performance of the device was studied experimentally over a cantilever test rig; the vibrating cantilever (0.4 m/s2) was excited by a motor operated at 30 Hz. The generated power successfully illuminated a light emitting diode (LED). The PZnT-NT generator produced a volume power density of 0.106 ± 0.011 μW/mm3 and a surface power density of 10.6 ± 1.1 μW/cm2. The performance of the proposed device with a size of (20 × 15 × 1 mm3) was higher in terms of power output than that of the commercial piezoelectric PbZrTiO3 (PZT) (63.5 × 31.8 × 0.51 mm3), microfiber composite (MFC) (80 × 57 × 0.335 mm3) and piezoelectric bimorph device (70 × 50 × 0.7 mm3). Compared to other existing ferroelectric and non-ferroelectric generators, the proposed device demonstrated exceptional performance in harvesting the energy at low acceleration and in a low-frequency environment. Moreover, the performance of the proposed PZnT-NT as well as the commercial MFC and PZT bimorph was studied systematically over the Vertical Axis Wind Turbine (VAWT) beam, which was located above an exhaust air outlet of the cooling tower system. For successful implementation of the harvester on an operating VAWT beam, good harvester location which is rich in vibration energy must be known in a priori to avoid poor power generation at a bad location. Thus, an optimal location selection scheme using two non-destructive vibration techniques, i.e., the Experimental Modal Analysis (EMA) and Operating Deflection Shape (ODS) analysis techniques were adopted to measure the dynamic characteristics and visualise the operating vibration shape of the system. The results showed that the highest displacement was located at the free end (near the rotor part of the VAWT). Furthermore, higher vibration was observed in the horizontal movement compared to the vertical movement of the VAWT beam. As a result, the PZnT-NT generator produced the highest volume power density (i.e. 0.107 ± 0.008 μW/mm3) compared to the PZT (i.e. 0.036 ± 0.005 μW/mm3), MFC (i.e. 0.007 ± 0.001 μW/mm3) and PZT bimorphs (i.e.0.006 ± 0.001μW/mm3). The power density was improved by 66%, 93.8% and 94% using the proposed PZnT-NT over the PZT, MFC and the PZT bimorph respectively. Furthermore, PZnT-NT was the most cost-effective solution in term of the highest power generated per dollar, (μW/mm3 $) ×105 (i.e. 7066.7±733.3), compared to PZT (i.e. 22.1±1.4), MFC (i.e. 4.3 ± 0.4) and PZT bimorph (i.e. 35.0±5.0). This has verified the great potential of PZnT-NT materials in harvesting useful energy from the VAWT beam.